In the Process of Educational Diagnosis of and Educational Intervention in Specific Learning Difficulties: Primary School Teachers’ Opinions and Experiences - Kuruyer, Hayriye Gül; Ahmet Çakıroğlu (European Journal of Multidisciplinary Studies, 2017)
Students with a specific learning difficulty are students with low achievement and difficulties in the fields of reading, comprehension and language use, writing, listening, thinking, speaking, or mathematical thinking and operational skills. Identification of specific learning difficulties is the first stage in the development of educational intervention programs. In order to be able to make regulations, it is necessary to determine the strengths and weaknesses of these students in terms of their educational needs. Therefore, it is important to explore primary school teachers’ experiences and classroom applications as well opinions and knowledge about the concept of specific learning difficulty and students having such difficulties because determination of interventions to be made to improve a state depends to a great extent on knowledge about the issue. Thus, the purpose of the current study is to explore primary school teachers’ opinions and applications related to educational diagnosis and education intervention processes followed in case of specific learning difficulties. A grounded theory methodology was used. The study group of the current research consists of 8 primary school teachers. The data were collected through semi-structured interviews and observations. The collected data were analyzed by means of the constant comparison method. The analysis yielded four super categories: specific learning difficulty, problems, tasks and process. As a result of the study, it can be maintained that the primary school teachers have both knowledge deficiencies as regards the educational diagnosis of specific learning difficulties and development of educational intervention programs and conceptual fallacies that make diagnosis more difficult. In addition, it was observed that the teachers experienced difficulties in the process of development and application of educational intervention programs.
Keywords: In the Process of Educational Diagnosis of and Educational Intervention in Specific Learning DifficultiesPrimary School Teachers’ Opinions and Experiences